A case report of hepatocarcinoma-originated pericardial malignancy - Wu, Bin; Wang, Zhixiao; Lin, Weizhe; Xiong, Jian; He, Chaoyong (Frontiers in Cardiovascular Medicine, 2025)
Cardiac tumors constitute an exceptionally rare neoplastic entity posing significant diagnostic challenges. We report a 55-year-old female patient without prior oncologic history who presented with acute-onset bilateral lower extremity edema progressing over 72 h. Transthoracic echocardiography demonstrated a pericardial mass with concomitant hemorrhagic pericardial effusion. Subsequent magnetic resonance imaging and systemic positron emission tomography localized the lesion to the right bottom of the heart. Surgical exploration suggested a cardiac occupancy as an irregular, fish-flesh-like soft tissue mass, pathology biopsy was performed suggesting a malignant tumour of epithelial origin, and immunohistochemistry was suggestive of hepatic origin. The patient received combination therapy comprising programmed death-1 inhibitor camrelizumab (200 mg via intravenous infusion every 21 days) and oral lenvatinib (8 mg once daily). Serial contrast-enhanced computed tomography of the thorax and abdomen demonstrated progressive metastatic dissemination with malignant pleural and peritoneal effusion formation. Despite therapeutic intervention, the patient ultimately experienced disease progression culminating in mortality.